The Gardener’s Practical Knowledge: The importance of time, reflection and knowledge of a place to become a site builder - Pihlgren, Paula (FormAkademisk, 2023)
With this article, I want to raise questions about the gardener’s practical knowledge in order to create greater awareness in educational contexts and working life of the importance and application of what it means to be and work as a gardener. Practical knowledge takes time to develop and requires experience and conscious reflection. It also requires knowledge of the particular site you are working with, which in principle is always complex, as it involves everything from natural habitats to human expressions, such as history. To understand what practical knowledge is, I drew on situations from my working life and discuss these with references that highlight the importance of involving different forms of knowledge, phenomenology and hermeneutics. I used the concept of genius loci to formulate the meaning of places and posthumanist thoughts on the relationship between humans and nature. My conclusion is that experience, reflection and knowledge of a place are central to building sites, a task in which the gardener is highly involved. I conclude with a number of questions about how to work with these aspects of the profession in education and working life.